Eating habits, food consumption, and health: The role of early life experiences - Effrosyni Adamopoulou; Elisabetta Olivieri; Eleftheria Triviza (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
This study explores the long-run effects of a temporary scarcity of a consumption good on preferences towards that good once the shock is over. Specifically, we focus on individuals who were children during World War II and assess the consequences of the temporary drop in meat availability they experienced early in life. To this end, we combine new hand-collected historical data on the number of livestock at the local level with microdata on eating habits, health outcomes, and food consumption expenditures. By exploiting cohort and regional variation in a difference-in-differences estimation, we show that individuals who as children were more exposed to meat scarcity tend to consume relatively more meat and spend more on food during late adulthood. Consistent with medical studies on the side effects of meat overconsumption, we also find that these individuals have a higher probability of being obese, having poor self-perceived health, and developing cancer. The effects are larger for women and persist intergenerationally, as the adult children of mothers who experienced meat scarcity similarly tend to overconsume meat. Our results point towards a behavioral channel, where early-life shocks shape eating habits, food consumption, and adult health.
Keywords: D12; I10; N44; 330; preferences; food consumption; early life experiences; gender differences